2022
DOI: 10.21577/0103-5053.20220033
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and SARS-CoV-2 3CL Protease Inhibitory Effects of Oxazolidinone Derivatives

Abstract: The 3-chymotrypsin-like protease (3CLpro) is an attractive target for the development of anti- SARS (severe acute respiratory syndrome) drugs. In this work, a series of oxazolidinone derivatives 3a-3v were synthesized and their inhibitory activities against SARS coronavirus 2 (SARS-CoV-2) 3CLpro were evaluated by the fluorescence resonance energy transfer (FRET)-based enzymatic assay. Among synthesized compounds, 3g displayed the best inhibitory activity, with a half maximal inhibitory concentration (IC50) val… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…Nelson et al proved their hypothesis which believed that the role of LNZ may be due to an interaction between (R and S)-linezolid with receptor-binding domain (RBD) of SARS-CoV-2 spike protein complexed with human angiotensin converting enzyme2 (ACE2). This opinion was proven using electronic and molecular docking [17]. Shengxian Zhao et al were synthesized 22 compounds of oxazolidinones derivatives (3a-3v) and screened them.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Nelson et al proved their hypothesis which believed that the role of LNZ may be due to an interaction between (R and S)-linezolid with receptor-binding domain (RBD) of SARS-CoV-2 spike protein complexed with human angiotensin converting enzyme2 (ACE2). This opinion was proven using electronic and molecular docking [17]. Shengxian Zhao et al were synthesized 22 compounds of oxazolidinones derivatives (3a-3v) and screened them.…”
Section: Introductionmentioning
confidence: 99%
“…They found that compound 3 g displayed the most potent inhibitory activity with an IC 50 value of 14.47 μmol·L −1 . Molecular docking analysis showed the modes of action of compound 3 g with 3-chymotrypsin-like protease (3CLpro) which responsible for cutting at least 11 sites and is extremely important for coronavirus replication [17]. Therefore, 3CLpro is an ideal target for the development of anti-coronavirus drug [17].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation